Cathepsin L in COVID-19: From Pharmacological Evidences to Genetics - Gomes, Caio P.; Fernandes, Danilo E.; Casimiro, Fernanda; da Mata, Gustavo F.; Passos, Michelle T.; Varela, Patricia; Mastroianni-Kirsztajn, Gianna; Pesquero, João Bosco (Frontiers in Cellular and Infection Microbiology, 2020)
The coronavirus disease 2019 (COVID-19) pandemics is a challenge without precedent for the modern science. Acute Respiratory Discomfort Syndrome (ARDS) is the most common immunopathological event in SARS-CoV-2, SARS-CoV and MERS-CoV infections. Fast lung deterioration results of cytokine storm determined by a robust immunological response leading to ARDS and multiple organ failure. Here, we show cysteine protease Cathepsin L (CatL) involvement with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and COVID-19 from different points of view. CatL is a lysosomal enzyme that participates in numerous physiological processes, including apoptosis, antigen processing and extracellular matrix remodeling. CatL is implicated in pathological conditions like invasion and metastasis of tumors, inflammatory status, atherosclerosis, renal disease, diabetes, bone diseases, viral infection and other diseases. CatL expression is up-regulated during chronic inflammation and is involved in degrading extracellular matrix, an important process for SARS-CoV-2 to enter host cells. In addition, CatL is probably involved in processing SARS-CoV-2 spike protein. As its inhibition is detrimental to SARS-CoV-2 infection and possibly exit from cells during late stages of infection, CatL could have been considered a valuable therapeutic target. Therefore, we describe here some drugs already in the market with potential CatL inhibiting capacity that could be used to treat COVID-19 patients. In addition, we discuss the possible role of host genetics in the etiology and spreading of the disease.